Molecular basis for the explanation of the exponential growth of polyelectrolyte multilayers - Picart, C. (The National Academy of Sciences, 2002)
The structure of poly(l-lysine) (PLL)/hyaluronan (HA) polyelectrolyte multilayers formed by electrostatic self-assembly is studied by using confocal laser scanning microscopy, quartz crystal microbalance, and optical waveguide lightmode spectroscopy. These films exhibit an exponential growth regime where the thickness increases exponentially with the number of deposited layers, leading to micrometer thick films. Previously such a growth regime was suggested to result from an “in” and “out” diffusion of the PLL chains through the film during buildup, but direct evidence was lacking. The use of dye-conjugated polyelectrolytes now allows a direct three-dimensional visualization of the film construction by introducing fluorescent polyelectrolytes at different steps during the film buildup. We find that, as postulated, PLL diffuses throughout the film down into the substrate after each new PLL injection and out of the film after each PLL rinsing and further after each HA injection. As PLL reaches the outer layer of the film it interacts with the incoming HA, forming the new HA/PLL layer. The thickness of this new layer is thus proportional to the amount of PLL that diffuses out of the film during the buildup step, which explains the exponential growth regime. HA layers are also visualized but no diffusion is observed, leading to a stratified film structure. We believe that such a diffusion-based buildup mechanism explains most of the exponential-like growth processes of polyelectrolyte multilayers reported in the literature.